Criterion validity of the general factor of psychopathology in a prospective study of girls. (23rd July 2014) - Lahey, Benjamin B.; Rathouz, Paul J.; Keenan, Kate; Stepp, Stephanie D.; Loeber, Rolf; Hipwell, Alison E.
Abstract : Background: The best‐fitting model of the structure of common psychopathology often includes a general factor on which all dimensions of psychopathology load. Such a general factor would be important if it reflects etiologies and mechanisms shared by all dimensions of psychopathology. Nonetheless, a viable alternative explanation is that the general factor is partly or wholly a result of common method variance or other systematic measurement biases. Methods: To test this alternative explanation, we extracted general, externalizing, and internalizing factor scores using mother‐reported symptoms across 5–11 years of age in confirmatory factor analyses of data from a representative longitudinal study of 2, 450 girls. Independent associations between the three psychopathology factor scores and teacher‐reported criterion variables were estimated in multiple regression, controlling intelligence, and demographic covariates. Results: The model including the general factor fit significantly better than a correlated two‐factor (internalizing/externalizing) model. The general factor was robustly and independently associated with all measures of teacher‐reported school functioning concurrently during childhood and prospectively during adolescence. Conclusions: These findings weaken the hypothesis that the general factor of psychopathology in childhood is solely a measurement artifact and support further research on the substantive meaning of the general factor.